(untitled) (Journal of Global Accounting, 2023)
This study examined the effects of tax leakages on economic development of Nigeria during the period 2008-2017. Specifically, it investigated how tax evasion and avoidance influenced economic development measured by gross domestic product per capita, infant mortality and life expectancy. In pursuit of the objectives of this study, three hypotheses were formulated and tested using secondary data obtained from the Central Bank of Nigeria, Federal Inland Revenue Service, World Bank Statistical Bulletins and National Bureau of Statistics. This study is based on time series data. The Augmented Dickey Fuller was used to test the time series data for stationarity. Ordinary Least Square regression was employed in the analysis of the data. The findings of this study confirmed that tax leakage has a significant negative effect on economic development in Nigeria at 5% level of significance. On the basis of the findings, it was recommended among others that federal government should judiciously make use of tax proceeds to provide basic amenities for the citizens, such as health care, school and so on; as this would curb the rate of infant mortality and improve the rate of tax compliance among the tax payers.